Dielectric breakdown model for conductor-loaded and insulator-loaded composite materials - Bergero, P. (2004)
The dielectric breakdown model to describe the dielectric breakdown patterns in both conductor-loaded and insulator-loaded composites was generalized. With a variable concentration p, particles were distributed at random in a matrix. According to particle characteristics, the generalized model assigned different probabilities to breakdown channel formation. The fractal dimension D and the parameters of the Weibull distribution was used to characterize the dielectric breakdown patterns.